2016
DOI: 10.1111/luts.12151
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Persistence with Mirabegron versus Solifenacin in Women with Overactive Bladder: Prospective, Randomized Trial

Abstract: This study demonstrated low persistence rates over 12 months for both mirabegron and solifenacin, although the reasons for discontinuation were somewhat different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 23 publications
4
38
1
Order By: Relevance
“…[13][14][15][16][17][18][19] A smallscaled study at a urology clinic reported a low persistence rate with mirabegron (12.2%; n = 76) and solifenacin (20.1%; n = 72). [13][14][15][16][17][18][19] A smallscaled study at a urology clinic reported a low persistence rate with mirabegron (12.2%; n = 76) and solifenacin (20.1%; n = 72).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] A smallscaled study at a urology clinic reported a low persistence rate with mirabegron (12.2%; n = 76) and solifenacin (20.1%; n = 72). [13][14][15][16][17][18][19] A smallscaled study at a urology clinic reported a low persistence rate with mirabegron (12.2%; n = 76) and solifenacin (20.1%; n = 72).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent reason for the discontinuation of mirabegron treatment was “no change or aggravated symptoms.” Although direct comparisons are inappropriate, this is broadly consistent with previous studies of mirabegron treatment persistence in the UK (in which “lack of efficacy” was the most common reason) and in Japan (in which “ineffectiveness” was the most common reason) . Furthermore, in a prospective trial of mirabegron versus solifenacin in female patients with OAB, discontinuation due to “lack of efficacy” was significantly more frequent for mirabegron compared with solifenacin (36.8% vs 5.6%, respectively), whereas discontinuation due to “side‐effects” was significantly more frequent for solifenacin compared with mirabegron (27.3% vs 7.9%, respectively) . In a post‐marketing study of solifenacin, “symptom remission” was the most frequent reason for treatment discontinuation during the 2‐year observation period, which may reflect the high efficacy rate for solifenacin during the same period of this study (84.7%)…”
Section: Discussionmentioning
confidence: 99%
“…32 In a study of female Japanese patients, the 12-month persistence rate was 12% for 76 patients receiving mirabegron, compared with 20% of 72 patients receiving solifenacin. 33 In contrast, an as yet unpublished retrospective cohort study of 3872 Japanese patients demonstrated higher persistence among patients receiving mirabegron compared with solifenacin, fesoterodine, tolterodine, imidafenacin, and propiverine. 34 Other currently unpublished studies conducted at single institutions have demonstrated that mirabegron persistence was significantly higher compared with anticholinergic agents.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent prospective, randomized trial on long-term persistence with Mir versus another antimuscarinic drug, solifenacin, showed that discontinuation as a result of TEAEs was significantly less frequent in the Mir group than the solifenacin group (7.9% vs 27.3, P < 0.05) over 12 months. 33 Furthermore, a recent retrospective, longitudinal, observational study of anonymized data from the UK Clinical Practice Research Datalink GOLD database on 21 996 patients aimed to compare persistence and adherence with Mir versus Tol ER and other antimuscarinics in routine clinical practice over a 12-month period, showed that 12-month persistence rates were significantly increased with Mir compared with all antimuscarinics. 34 The main limitation of the present review was the 12 months design of most of the studies.…”
Section: Discussionmentioning
confidence: 99%